A atuação do UNICEF na educação pública brasileira - Nolasco, Isabela [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The research investigates the performance of the United Nations Children's Fund (UNICEF) related to Brazilian public education during the last five years. The proposal of the theme arose from an experience of international exchange between the Paulista State University Júlio de Mesquita Filho (UNESP) and Patras University- Greece. Through this experience I had the opportunity to meet UNICEF headquarters in the city of Geneva, Switzerland, which has shown great relevance through the performance of the organ in the last 70 years of existence. The opportunity to study abroad opened my eyes to see the enormous influence of international organizations that work in the field of education and aroused in me, a great interest to search deeper the interventions of UNICEF in Brazil. Thus, the research aims to map the main fronts of UNICEF action in Brazilian public education, seeking to scale the areas of greatest influence in the fight for the rights of children and adolescents. I propose to carry out a qualitative research through documentary and bibliographic analysis, using UNICEF annual Brazilian digital reports from 2012 to 2016, responsible for the dissemination of the main actions of the year, financial investments and the institutions supported, in addition I am counting on the publication of the UNICEF national news media from the last five years. In this way, in the respective study, I will identify the areas of human rights protection of children and adolescents that are being provided by UNICEF; analyze the strategies of the programs and projects in which the agency has operated and investigate the priority regions in Brazil. Finally, I want to contribute in parallel with authors who articulate in the field of global policies of education, for the advancement of a society that prioritizes above all the child and education

A pesquisa investiga a atuação do Fundo das Nações Unidas para Infância (UNICEF) frente a educação pública brasileira nos últimos cinco anos. A proposta da temática surgiu a partir de uma experiência de intercâmbio internacional vinculado à Universidade Estadual Paulista Júlio de Mesquita Filho (UNESP) e a Universidade de Patras - Grécia. Por meio dessa vivência tive a oportunidade de conhecer a sede do UNICEF na cidade de Genebra, na Suíça, o qual evidenciou grande relevância mediante o desempenho do órgão nos últimos 70 anos de existência. A oportunidade de estudar fora abriu meus olhos para enxergar a enorme influência de organizações internacionais que atuam no âmbito da educação e despertou em mim, grande interesse em conhecer a fundo as intervenções do UNICEF no Brasil. Sendo assim, a pesquisa objetivou mapear as principais frentes de atuação do UNICEF na educação pública brasileira, buscando dimensionar os âmbitos de maior influência na luta dos direitos da criança e do adolescente. Assim, foi realizado uma pesquisa de natureza qualitativa por meio de análise bibliográfica e documental, utilizando os relatórios brasileiros anuais digitais do UNICEF dos anos de 2012 a 2016, incumbidos pela divulgação das principais ações do ano, pelos investimentos financeiros e pelas instituições apoiadas, além da publicação digital do banco de notícias da imprensa nacional do UNICEF dos últimos cinco anos. Desta forma, no respectivo estudo foi identificado as áreas de proteção dos direitos humanos da criança e do adolescente que vêm sendo assegurados pelo UNICEF, as estratégias de programas e projetos em que órgão tem operado e as regiões de atuação prioritárias no território brasileiro. Almejo por fim, ter contribuído em paralelo com autores que articulam no campo de políticas globais de educação, para o avanço de uma sociedade que prioriza acima de tudo a criança e a educação
Keywords: UNICEF; Educação e Estado; Educação; Políticas públicas; Direitos das crianças; Direitos dos adolescentes; Brasil - 2012-2016